2020
DOI: 10.5194/nhess-20-2997-2020
|View full text |Cite
|
Sign up to set email alerts
|

Are flood damage models converging to “reality”? Lessons learnt from a blind test

Abstract: Abstract. Effective flood risk management requires a realistic estimation of flood losses. However, available flood damage estimates are still characterized by significant levels of uncertainty, questioning the capacity of flood damage models to depict real damages. With a joint effort of eight international research groups, the objective of this study was to compare, in a blind-validation test, the performances of different models for the assessment of the direct flood damage to the residential sector at the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 48 publications
(102 reference statements)
3
40
0
Order By: Relevance
“…Additionally, flood preparedness evolved over time, documented, for example, by Kienzler et al (2015) and Thieken et al (2016) for Germany. Economic situations may also change the relative value of exposed assets and its recover or repair costs (Penning-Rowsell, 2005;Kron, 2005). Such changes are challenging to include in loss models, however.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, flood preparedness evolved over time, documented, for example, by Kienzler et al (2015) and Thieken et al (2016) for Germany. Economic situations may also change the relative value of exposed assets and its recover or repair costs (Penning-Rowsell, 2005;Kron, 2005). Such changes are challenging to include in loss models, however.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the transferability of the damage model, literature shows that the performance of foreign models can be affected by high levels of error, with overestimation from two to eleven times (Molinari et al, 2020, Scorzini andFrank, 2017). So, for the Italian case study, the overestimation of 3.15 times is not unacceptable.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…Damage estimation was limited to direct damage to residential buildings and agriculture in order to implement models specifically calibrated in the context under investigation and to avoid the spatial transfer of foreign models. This could have compromised the reliability of damage estimation (Cammerer et al 2013;Molinari et al 2020), above all in absence of data for validation. Exhaustiveness of damage assessment is also limited here by the disregard of systemic and indirect damages like loss of property value because of the flood, damages due to business disruption, ripple effects and others.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a synthetic micro-scale multi-variable model that presents the advantage of an explicit formulation and a user-friendly implementation, still implicitly maintaining the dependence of the original model from a large number of hazard ( 6) and vulnerability ( 18) parameters. The INSYDE model has been validated for the 2002 flood in Lodi by Molinari et al (2020). Galliani et al (2020) demonstrated that the use of simple-INSYDE leads to comparable results and does not decrease much the accuracy of the damage forecast compared to the full version of the model.…”
Section: Damage Modelling For the Residential Sector: Simple-insydementioning
confidence: 99%